2012
DOI: 10.1038/nature11073
|View full text |Cite
|
Sign up to set email alerts
|

The intense starburst HDF 850.1 in a galaxy overdensity at z ≈ 5.2 in the Hubble Deep Field

Abstract: The Hubble Deep Field (HDF) is a region in the sky that provides one of the deepest multi-wavelength views of the distant universe and has led to the detection of thousands of galaxies seen throughout cosmic time 1 . An early map of the HDF at a wavelength of 850 microns that is sensitive to dust emission powered by star formation revealed the brightest source in the field, dubbed HDF850.1 2 . For more than a decade, this source remained elusive and, despite significant efforts, no counterpart at shorter wavel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
354
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 282 publications
(390 citation statements)
references
References 55 publications
29
354
6
1
Order By: Relevance
“…τ [CII] 1). The observed L [CII] and predicted L CO(1-0) by Walter et al (2012), yield a L [CII] /L CO(1-0) ratio of ∼ 5200, in agreement with the ratio derived from the SPT sample of 5200 ± 1800 ( § 4.4). We now generalise this line ratio method by comparing the source functions.…”
Section: Determining the Optical Depth Of The [Cii] Linesupporting
confidence: 67%
See 2 more Smart Citations
“…τ [CII] 1). The observed L [CII] and predicted L CO(1-0) by Walter et al (2012), yield a L [CII] /L CO(1-0) ratio of ∼ 5200, in agreement with the ratio derived from the SPT sample of 5200 ± 1800 ( § 4.4). We now generalise this line ratio method by comparing the source functions.…”
Section: Determining the Optical Depth Of The [Cii] Linesupporting
confidence: 67%
“…Maiolino et al 2005;Stacey et al 2010;Wang et al 2013), while others have been selected as starburst galaxies (e.g. Ivison et al 2010;Hailey-Dunsheath et al 2010;Stacey et al 2010;Cox et al 2011;Swinbank et al 2012;Walter et al 2012;Riechers et al 2013;Brisbin et al 2015). This leads to a heterogeneous sample of high-z [CII] detections, containing a mixture of AGN and starburst-dominated systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources with z > ∼ 2 are primarily identified via Lyα emission and sources at z < ∼ 1.3 are identified via OII, OIII or Hα. An updated version of the Chapman et al redshift distribution is shown as a dashed-blue line, including DEIMOS-observed radio SMGs from Banerji et al (2011) specifically targeted to fill the redshift desert gap of LRIS, and a handful of high-z 850µm-selected SMGs Daddi et al, 2009;Walter et al, 2012). Also over-plotted is the Lewis et al (2005) and Chapman et al (2003b) phenomenological model 850µm SMG redshift distribution without radio flux selection (dark green dot dashed line).…”
Section: Redshift Distributions Of 850µm-14 Mm-selected Dsfg Populatmentioning
confidence: 99%
“…We identified them as CO(5-4) and CO(6-5), which placed the source at z=5.183, as confirmed by follow-up observations of the CO(2-1) and [CII] lines (Walter et al 2012;Neri et al 2014). This was the first spectroscopic redshift measurement for this iconic source (14 years after its discovery by Hughes et al 1998).…”
Section: A Molecular Scan In the Hdf-nmentioning
confidence: 82%